PENGABDIAN KEPADA MASYARAKAT PENDIDIKAN KESEHATAN BANTUAN HIDUP DASAR - Komang Agus Jerry Widyanata; I Made Sukma Wijaya; Kurniasih Widayati (Jurnal Pengabdian kepada Masyarakat Wahana Usada, 2019)
Every two minutes one person dies of cardiac arrest. death rates can  be prevented if the victim gets immediate assistance, if someone who is trained in pulmonary cardiac resuscitation (CPR) provides basic life support until medical assistance takes over. Basic life support can be done by anyone and anywhere as soon as possible at the beginning of the occurrence of cardiac arrest to increase survival. This activity aims to provided health education to the community so that they can know and demonstrate how to provide basic life support in cases of cardiac arrest. Methods: Health education uses the lecture method of discussion accompanied by demonstration with power point media which is assisted with LCD and projector for 30 minutes then followed by demonstration using CPR manikin(Cardiopulmonary Resuscitation) for 10 minutes. A sample size of 30 people in Br. Tek-Tek, Desa Peguyangan, Denpasar Utara with accidental sampling technique. Results: The minimum results achieved are 80% at the point of practicing how to provide pulmonary heart resuscitation and a value of 100% is at 2 points of each evaluation which mentions the meaning of basic life support and mentions the steps of basic life support, while for indications and contraindications from basic life support 90% of participants were able to mention it. Conclusion: Health education program activities and demonstrations about basic life support that have been implemented are very useful to increase knowledge and are expected to be able to practice and provide first aid in cases of respiratory arrest and cardiac arrest.